O библиографическом методе - Janonis, Osvaldas (Knygotyra, 2024)
In this article, the discussion with M. G. Vochryševa about the bibliographical method and its co-scientific status is investigated. The author thinks that the given arguments are weak and erroneous. The creation of special scientific bibliographical methods is the task of the future. The perspectives for this are opened by the developing general theory of bibliography.